Windows on justice in northern Iberia, 800-1000 - Davies, Wendy, 1942-, author.
1 online resource (175 pages)
Keywords: "Although it has a rich historiography, and from the late ninth century is rich in textual evidence, northern Iberia has barely featured in the great debates of early medieval European history of recent generations. Lying beyond the Frankish world, in a peninsula more than half controlled by Muslims, Spanish and Portuguese experience has seemed irrelevant to the Carolingian Empire and the political fragmentation (or realignment) that followed it. But Spain and Portugal shared the late Roman heritage which influenced much of Western Europe in the early Middle Ages and by the tenth century political practice in the Christian North had plenty of features in common with parts to the east"--Provided by publisher.